Pelatihan Urban Farming Sebagai Solusi Ruang Terbuka Hijau di Kampung Nagrek Desa Sampora Tangerang Dengan Support Digital Platform Artemis - Riana Magdalena Silitonga; Stefani Prima Dias Kristiana; Ronald Sukwadi (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2026)
Tangerang with high population growth coupled with rapid development often changes the natural configuration of the land to the detriment of the existence of Green Open Space (RTH). The existing Tangerang Regency open green space is only 8% or 80.14 km2. Nagrek village, Sampora village, Tangerang was chosen because the area is a dense settlement that lacks green space and has a group of non-productive housewives. Policies that can be carried out to restore environmental conditions and overcome green space issues in Nagrek Village are by implementing an urban farming program with a conventional farming system and a hydroponic axis system by involving non-productive housewives. The method of implementing urban farming training is carried out with 5 stages, namely the stages of preparation, outreach, training, mentoring and evaluation. The recruitment phase of the activity implementation team and the measurement of the results of community service are recorded in the Artemis digital platform. The results of the urban farming training activities in the Nagrek Village Sampora Village Tangerang received a response that Nagrek Village looks more beautiful than before. Many non-participant residents began to be interested in participating in implementing the urban farming program in their own homes.